Chimeric Antigen Receptor (CAR)-T Cell Therapy for Non-Hodgkin's Lymphoma - Maria Giraudo; Zachary Jackson; Indrani Das; Olubukola Abiona; David Wald (Case Western Reserve University, 2024)
This review focuses on the use of chimeric antigen receptor (CAR)-T cell therapy to treat non-Hodgkin's lymphoma (NHL), a classification of heterogeneous malignant neoplasms of the lymphoid tissue. Despite various conventional and multidrug chemotherapies, the poor prognosis for NHL patients remains and has prompted the utilization of groundbreaking personalized therapies such as CAR-T cells. CAR-T cells are T cells engineered to express a CAR that enables T cells to specifically lyse tumor cells with extracellular expression of a tumor antigen of choice. A CAR is composed of an extracellular antibody fragment or target protein binding domain that is conjugated to activating intracellular signaling motifs common to T cells. In general, CAR-T cell therapies for NHL are designed to recognize cellular markers ubiquitously expressed on B cells such as CD19+, CD20+, and CD22+. Clinical trials using CAR-T cells such as ZUMA-7 and TRANSFORM demonstrated promising results compared to standard of care and ultimately led to FDA approval for the treatment of relapsed/refractory NHL. Despite the success of CAR-T therapy for NHL, challenges include adverse side effects as well as extrinsic and intrinsic mechanisms of tumor resistance that lead to suboptimal outcomes. Overall, CAR-T cell therapies have improved clinical outcomes in NHL patients and generated optimism around their future applications.